Design of a class-EF inverter - Jiang, Haoquan (Nanyang Technological University, 2024)
This dissertation focuses on the design and analysis of load-independent Class EF inverters for high-frequency wireless power transfer (WPT) applications. Three distinct inverter topologies are examined: the basic Class EF inverter, the Class EF inverter with Series-Series (SS) compensation, and a simplified Class EF inverter with SS compensation. The goal is to evaluate the performance of these circuits under varying load conditions and to determine the effectiveness of SS compensation in minimizing harmonic distortion and maintaining output voltage stability. Simulations were conducted using LTspice, and the results are analyzed in terms of output voltage amplitude and Total Harmonic Distortion (THD). The study demonstrates that the SS compensated Class EF inverter exhibits superior stability and lower THD, making it a more reliable solution for wireless power transfer systems. The simplified circuit, though slightly less efficient, offers a more streamlined design with reduced component count.